Case Report: Gastric cancer with chondromyxoid matrix similar matrix-producing metaplastic breast carcinoma: report of an undescribed entity - Wu, Xiaoyan; He, Huihua; Zhao, Lina; Zeng, Zhi; Yuan, Jingping (Frontiers in Oncology, 2023)
Gastric cancer is a malignant epithelial neoplasm of the stomach, including adenocarcinoma, squamous cell carcinoma, adenosquamous carcinoma, undifferentiated carcinoma, gastroblastoma and neuroendocrine neoplasms, without gastric metaplastic carcinoma. We describe a 69-year-old male patient with gastric cancer who presented with a novel, biphasic histologic morphology with one component consisting of poorly differentiated adenocarcinoma and the other component consisting of chondromyxoid matrix with adenocarcinoma transition to, between the two components without a spindle cell component. The histological morphology of this case is similar to matrix-producing metaplastic breast carcinoma. Therefore, we diagnose this case as gastric carcinoma with chondromyxoid matrix similar matrix-producing metaplastic breast carcinoma.